Immunohistochemical expression of cyclin D1 in invasive breast carcinoma and its correlation with clinicopathological parameters - Pranoti Vitthalrao Lengare; Siddhi Gaurish Sinai Khandeparkar; Avinash R Joshi; Bageshri P Gogate; Smita Ganeshrao Solanke; Sujit Hanumant Gore (Wolters Kluwer Medknow Publications, 2020)
Introduction: Breast cancer (BC) is the most common cancer and leading cause of death in women. Aim: This study was conducted to study the cyclin D1 expression in BC and its correlation with other clinicopathological parameters such as tumor size, histological grade, lymph node status, estrogen receptor (ER), progesterone receptor (PR), HER2/neu, and Ki67 status. Materials and Methods: Fifty cases of BC diagnosed between 2015 and 2018 were included in the study. A technique of manual tissue microarray was employed for the analysis of expression of immunohistochemical (IHC) markers such as cyclin D1, ER, PR, HER2/neu, and Ki67 in all cases. Results were subjected to statistical analysis. Results: Cyclin D1 positivity was seen in 64% cases of BC cases of which 8% were triple negative BC (TNBC) molecular subtype. Cyclin D1 expression was statistically significantly associated with ER and PR positivity. Maximum cases showing cyclin D1 expression showed negative HER2/neu expression, Ki67 immunopositivity, absent lymphovascular invasion and were of lower grade and stage. 32% cases were TNBC. Cyclin D1 was found positive in 25% TNBC cases. Negative Cyclin D1 expression was seen in TNBC cases of higher grade and higher stage with positive lymph node status, presence of lymphovascular invasion and Ki67 positivity. Conclusion: Cyclin D1 can be potentially used as a prognostic marker and if included in routine IHC workup of BC cases can aid in appropriate patient management with the advent of new targeted therapy that blocks the cyclin D-CDK4/6 axis.